Examining Linear and Nonlinear Associations Between Negative Emotional Reactivity to Daily Events and Depression Among Adolescents. (July 2022) - Santee, Angela C.; Starr, Lisa R.
Existing research supports competing hypotheses about the link between negative emotional (NE) reactivity to daily events (e.g., hassles and uplifts) and depression. Some have suggested that depression is associated with blunted reactivity, and others have suggested that depression is associated with heightened reactivity. In this study, we tested linear and nonlinear associations, cross-sectionally and longitudinally, between NE reactivity and depression among a sample of 232 adolescents. Participants completed lab-based assessments of depression then rated their experience of emotions, daily hassles, and uplifts three times per day for 7 days. Interviews were readministered 1.5 years later. Results show a significant U-shaped relationship between NE reactivity to hassles and depression symptoms cross-sectionally, which suggests that depression is more severe at the extremes of NE reactivity. NE reactivity to daily uplifts showed significant linear associations, but not quadratic associations, with depression such that heightened reactivity to uplifts was associated with more severe depression symptoms concurrently and predicted worsening of depression longitudinally.